PROBLEMS OF CHOOSING INNOVATIVE STRATEGIES FOR THE EDUCATIONAL PROCESS BASED ON EMPIRICAL METHODS - Muratov Elvin Ilich (Scholar Express Journal, 2022)
When compiling a textbook, the main emphasis is on the rules for designing the educational process for professional educational programs in the current conditions. The features of the organization of educational activities of students, innovative teaching methods and educational technologies in vocational education are considered; principles, functions, means and methods of educational control and evaluation of the development of the educational program. Problems are encountered at the level of choosing the strategy of the educational process. Despite the large selection of practice-oriented, problematic and creative tasks, which gives freedom to choose the forms and methods of teaching, creates the flexibility of the educational process, it is still necessary to take into account the problems of choosing the educational process. This article proposes to solve this problem through empirical methods
Keywords: Education and pedagogy; organizational and pedagogical design; pedagogy; psychology